Era Uma Vez... Figurações do Arquétipo da Princesa e do Pater Familias em contos de Marina Colasanti - Gudino, Mariana Elizabeth Ceris Burtett (2024)
This dissertation develops an interpretative analysis of the tales "Um espinho de marfim," "Sete anos e mais sete," "Entre a espada e a rosa," and "Como um colar," published in the book "mais de 100 histórias maravilhosas" by Marina Colasanti (2015), focusing on the symbolic elements depicted in them. The research method is based on the assumptions of transdisciplinarity, intertwining theoretical contributions from comparative criticism and analytical psychology, considering the proximities, distances, and relationships between the tales in question. Our objective is to investigate the developments in the narratives featuring the topos of the princess and how the relationship between this figure and her father – the pater familias – who, in addition to being a father, is also the highest symbol of power in the figure of the king, evolves. Another objective is to establish connections between the archetypal representations of the feminine in the writer's tales and mythology, and to investigate the strategies employed by the princess characters to deal with the adversities of the plot. In this way, we build reflections on possible insights provided by the reading of the literary text and how these new insights can contribute to self-knowledge. The material gathered so far reveals, even if partially, that the intertextual update of the princess archetype in the selected tales is shaped by a more active and resilient feminine, reflecting the historical moment we are living, referred to by Whitmont (1991) as the return of the goddess.